Boards attributes and their implications on decision-making process - Ljubojević, Gordana; Dašić, Goran (Hotel and Tourism Management, 2018)
The results of the research presented in the paper are expected to confirm that all dimensions and aspects of the new model of corporate governance are present in the practice of companies in the Republic of Serbia, and that attributes of the board of directors, or the supervisory board of companies, considered in this paper, are present in accordance with the requirements of positive law and the practice of good corporate governance.